Factors associated with non-response to second course indomethacin for PDA treatment in preterm neonates. (3rd June 2018) - Louis, Deepak; Wong, Cindy; Ye, Xiang Y.; McNamara, Patrick J.; Jain, Amish
Abstract: Background: Failure of first course of indomethacin (FCI) for patent ductus arteriosus (PDA) treatment in preterm neonates often prompts clinicians to consider a second course (SCI). Objective: To identify factors including baseline characteristics and response to FCI that are associated with non-response to SCI for PDA treatment in preterm neonates. Methods: In this retrospective observational study, neonates ≤32 weeks admitted to a tertiary NICU over 5 years who received two indomethacin courses for PDA treatment were reviewed. Only neonates with echocardiograms (ECHO) immediately before and after receipt of each indomethacin course were included. Primary outcome was non-response to SCI. Baseline characteristics and response to FCI were compared between responders and non-responders of SCI. Results: Of the 98 neonates enrolled, 47 (48%) had non-response to SCI. Of them, 27 patients (57%) had prior non-response to FCI, while of the 51 neonates who responded to SCI, 24 neonates (47%) had prior non-response to FCI. The adjusted risk of non-response to SCI in patients who had non-response to FCI was 37% higher (relative risk = 1.37, 95%CI: 0.87–1.80; p  = .07) compared to those who had response to FCI. Multivariable analysis showed that increasing gestational age (AOR: 1.6, 95%CI: 1.1–2.3, p  = .03) was associated with a higher odds of non-response to SCI while the odds of non-response to SCI increased by 90% in patients with non-response to FCI (AOR: 1.9, 95%CI: 0.8–4.5; p  = .15) compared to those with success of FCI, although no statistical significance was observed. Conclusions: Advanced gestational age was the predictor of non-response to SCI in preterm neonates.